Empowering Communities Through Legal Counseling in Agrarian Reform: A Simojayan Village Case - Herlindah Herlindah; Jonathan Pascal Chrisananto; Rachel Olivia Pasaribu; Fransiskus Arya Kusuma Aji; Andhika Arya Tamtama; Dhianya Azzahra Jasmine (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Simojayan Village in Malang Regency has long experienced unresolved agrarian conflicts. Addressing these issues requires not only innovative legal strategies but also increased public legal awareness. In response, a legal outreach program was conducted, involving expert presentations and interactive dialogue, and attended by over 70 participants. The program successfully enhanced the community’s understanding of agrarian law, particularly regarding the legal status of former HGU lands and the opportunities presented by agrarian reform. A notable outcome of the outreach was the community’s initiative to form a citizen forum for agrarian advocacy and their commitment to collaborate with legal organizations, including the Forum of Law Students for Justice (FORMAH PK). Follow-up plans include legal counseling, participatory land mapping, and paralegal training. These results indicate that legal education can serve as an effective entry point for community empowerment and equitable conflict resolution.